The LspB Protein Is Involved in the Secretion of the LspA1 and LspA2 Proteins by Haemophilus ducreyi - Ward, Christine K. (American Society for Microbiology, 2004)
The LspA1 and LspA2 proteins of Haemophilus ducreyi 35000 are two very large macromolecules that can be detected in concentrated culture supernatant fluid. Both of these proteins exhibit homology with the N-terminal region of the Bordetella pertussis filamentous hemagglutinin (FHA), which is involved in secretion of the latter macromolecule. The lspA2 open reading frame is flanked upstream by a gene, lspB, that encodes a predicted protein with homology to the B. pertussis FhaC outer membrane protein that is involved in secretion of FHA across the outer membrane. The H. ducreyi lspB gene encodes a protein with a predicted molecular mass of 66,573 Da. Reverse transcription-PCR analysis suggested that the lspB gene was transcribed together with the lspA2 gene on a single mRNA transcript. Polyclonal H. ducreyi LspB antiserum reacted with a 64-kDa antigen present in the Sarkosyl-insoluble cell envelope fraction of H. ducreyi 35000, which indicated that the LspB protein is likely an outer membrane protein. Concentrated culture supernatant fluids from H. ducreyi lspB and lspA1 lspB mutants did not contain detectable LspA1 and detectable LspA2, respectively. However, complementation of the lspB mutant with the wild-type lspB gene on a plasmid restored LspB protein expression and resulted in release of detectable amounts of the LspA1 protein into culture supernatant fluid. When evaluated in the temperature-dependent rabbit model of infection, the lspB mutant was attenuated in the ability to cause lesions and was never recovered in a viable form from lesions. These results indicated that the H. ducreyi LspB protein is involved in secretion of the LspA1 and LspA2 proteins across the outer membrane.